2008
DOI: 10.1016/j.ejcts.2007.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Revascularization strategy in patients with multivessel disease and a major vessel chronically occluded; data from the CABRI trial

Abstract: In patients with multivessel coronary disease and chronic occlusion of a major epicardial vessel, achieving of a complete revascularization by reopening or bypassing the occluded vessel is associated with a significantly better long-term prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…In general, complete revascularization leads to better outcomes than incomplete revascularization. [413][414][415][416][417][418] In patients with chronic total occlusion, CABG could be preferable to PCI, 419 but this is still controversial. Although the technology and techniques for PCI of chronic total occlusions are improving, there remains no current evidence that survival is improved after successful PCI of a chronic total occlusion.…”
Section: Fihn Et Al Stable Ischemic Heart Disease: Full Text E391mentioning
confidence: 99%
“…In general, complete revascularization leads to better outcomes than incomplete revascularization. [413][414][415][416][417][418] In patients with chronic total occlusion, CABG could be preferable to PCI, 419 but this is still controversial. Although the technology and techniques for PCI of chronic total occlusions are improving, there remains no current evidence that survival is improved after successful PCI of a chronic total occlusion.…”
Section: Fihn Et Al Stable Ischemic Heart Disease: Full Text E391mentioning
confidence: 99%
“…However, this analysis was selected in the minority of randomly assigned patients (21.2%) with a major vessel chronically occluded. 14 The potential benefit of complete revascularization on long-term mortality in patients with multivessel CAD, undergoing PCI, or CABG was demonstrated in registry studies. Recently, Hannan et al analyzed, from the New York State's Percutaneous Coronary Interventions Report System (PCIRS), the impact of complete revascularization in more than 33 000 patients who underwent PCI with BMS or drug-eluting stents (DES).…”
Section: Discussionmentioning
confidence: 99%
“…Benefit was greatest among patients with more severe baseline ischemia [32,33]. Subgroup analysis of the Coronary Angioplasty versus Bypass Revascularization investigation (CABRI) trial, one of a few studies evaluating CABG and PCI in patients with CTOs, demonstrated that CABG had better outcomes in these patients with multi-vessel disease in terms of subsequent morality and risk of acute MI [34]. In post hoc study of the All-Comer SYNTAX Trial, the presence of a total occlusion was less likely to result in complete revascularization in the PCI and CABG arms, with this effect being substantially more pronounced in the PCI arm and incomplete revascularization, compared with complete revascularization, has a detrimental impact on long-term clinical outcome, including mortality [35].…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%